Digital minimalism choosing a focused life in a noisy world - Newport, Cal. (New York Portfolio/Penguin, 2019)
Learn how to switch off and find calm - from the New York Times bestselling author of A World Without Email 'Digital Minimalism is the Marie Kondo of technology' Evening Standard 'An eloquent, powerful and enjoyably practical guide to cutting back on screen time' The Times 'An urgent call to action for anyone serious about being in command of their own life' Ryan Holiday 'What a timely and useful book' Naomi Alderman, author of The Power Do you find yourself endlessly scrolling through social media or the news while your anxiety rises Are you feeling frazzled after a long day of endless video calls In this timely book, professor Cal Newport shows us how to pair back digital distractions and live a more meaningful life with less technology. By following a 'digital declutter' process, you'll learn to: Rethink your relationship with social media Prioritize 'high bandwidth' conversations over low quality text chains Rediscover the pleasures of the offline world Take back control from your devices and find calm amongst the chaos with Digital Minimalism.
Includes bibliographical references (pages 257-271) and index.
Keywords: Information technology--Social aspects